Tin Mineralization in the Triassic Chacaltaya District (Cordillera Real, Bolivia) Traced by In Situ Chemical and δ18O-δ11B Compositions of Tourmaline - Torró, L.; Harlaux, M.; Castro-Morante, A.; Vallance, J.; Tavazzani, L.; Bouvier, A.-S.; Bovay, T.; Chelle-Michou, C.; Sempéré, T.; Melgarejo i Draper, J.C. (Society of Economic Geologists, Inc, 2024)
Abstract We present a petrographic and geochemical study of tourmaline from the Triassic Chacaltaya Sn-polymetallic district in the Cordillera Real of Bolivia. Tourmaline is associated with greisens, breccias, and veins, which occur around the Triassic Chacaltaya peraluminous granitic stock hosted by Silurian metasedimentary rocks. Three main petrographic types of hydrothermal tourmaline have been identified: pre-ore greisen-related (Tur-1), syn-ore breccia-related (Tur-2), and syn-ore vein-related (Tur-3). The three types of tourmaline belong to the alkali group and have Fe-rich compositions mostly close to the schorl end member. Overlapping Fe/(Fe + Mg) ratios suggest broadly similar compositions of the hydrothermal fluids during the deposition of tourmaline. The most notable differences in minor and trace element contents include relative enrichment in Zn and Li in Tur-1 and relative enrichment in Ca, Sc, V, Cr, Sr, Sn, Y, Cs, Be, and Zr in Tur-3, with Tur-2 showing intermediate compositions between those of Tur-1 and Tur-3. The progressive enrichment in Sn from Tur-1 (avg = 14 ppm) through Tur-2 (avg = 311 ppm) and Tur-3 (avg = 476 ppm) indicates an increase of Sn concentrations in the hydrothermal system coinciding with cassiterite deposition in breccias and veins. The transition from high Li and Zn contents in Tur-1 to elevated Ca, Sr, V, and Cr contents in Tur-3 is interpreted as reflecting interaction between a hydrothermal fluid of magmatic origin and the metasedimentary country rocks. Strong and relatively steady positive Eu anomalies in all tourmaline types suggest dominantly reduced hydrothermal conditions. In situ δ18O and δ11B analyses of greisen-related Tur-1 reveal crystallization in isotopic equilibrium with magmatic water derived from a peraluminous S-type granite. In contrast, higher δ18O values of breccia-related Tur-2 and vein-related Tur-3 indicate crystallization in isotopic equilibrium with a fluid of metamorphic origin or a magmatic fluid that variably interacted with the metasedimentary host rocks. Geochemical modeling reproduces interactions between a fluid of magmatic origin and the host metasedimentary rocks at moderate water/rock ratios between 0.1 and 0.5. We conclude that cassiterite mineralization in the Chacaltaya district was formed primarily through interaction between B-Sn–rich magmatic fluids and the metasedimentary country rocks.
Keywords: Tourmaline; Breccia; Greisen; Geology; Cassiterite; Geochemistry; Petrography; Hydrothermal circulation; Mineralization (soil science); Skarn; Pegmatite; Tin; Mineralogy; Fluid inclusions; Chemistry; Paleontology; https://purl.org/pe-repo/ocde/ford#1.05.02